Role of Topical Human Milk in the Treatment of Neurotrophic Corneal Opacity - M. Arshad Mahmood, Munawar Ahmed, Muhammad Saeed (Pakistan Journal of Ophthalmology, 2018)
Purpose: To study the effect of topical human milk on neurotrophic corneal opacity. Material and Methods: This observational clinical analysis was done at Departments of Ophthalmology, Liaquat University of Medical & Health Sciences Jamshoro, Azra Naheed Medical College Lahore, and College of Medicine and Dentistry Lahore from June 2005 to June 2011 to determine effects of human milk on forty three (28 male and 15 female) patients within 55 years of age, having neurotrophic corneal opacity. Three patients were dropped due to incomplete follow up. Forty patients with neurotrophic cornea, sixteen non insulin dependent diabetics, and twenty four with previous viral keratitis were included in the study After taking informed consent these patients were put on topical human milk and tobramycin 0.3% eye drops four times daily. Before treatment every patient was seen on slit lamp to assess size, site, level and density of opacity. Thickness and vascularization of cornea, condition of endothelium, and any reaction in the anterior chamber was also noted. Corneal staining was done to rule out ulcer and tear strip along the inner border of lower lid was also noted to see the level of dryness associated with neurotrophic cornea. Best corrected visual acuity was recorded and corneal sensitivity was tested with a cotton tip. Sensitivity to chemical stimulation was also determined with diclofenac sodium eye drops by noting intensity of burning sensation. Follow up was done for six months, on day 7, day 15 and monthly. The beneficial and adverse effects were noted and results were compiled. Only forty patients who completed six months follow up were included in the final result analysis. Results: Treatment response began within 15 days of instillation of topical human milk, corneal sensitivity improved in 24 (60%) eyes and visual acuity improved in 28 (70%). Transient conjunctival hyperemia was noted in most of the patients. Out of forty patients (28 male 12 female) 32 patients (80%) achieved nearly complete recovery of corneal transparency by last follow up. 8 (20%) diabetic patients failed to respond completely. Bacterial conjunctivitis occurred in 6 (15%) patients. Conclusion: Human milk helps in restoring corneal transparency in neurotophic corneal opacity, especially in patients with previous viral keratitis.